ATURAN HUKUM TINDAK PIDANA GENG MOTOR OLEH ANAK: Di Desa Bangun Sari Baru Kecamatan Tanjung Morawa Perspektif Hukum Pidana Dan Hukum Islam - Pirata, Apas; Suriyati, Chairus; Indrayani, Leni; Maria, Juliya (MAQASHID, 2025)
Handling criminal acts involving children in motorcycle gangs is a crucial step regulated by national criminal law and Islamic law with an emphasis on child protection and moral development and the future of these children. The purpose of this study is to evaluate existing legal regulations, identify challenges in their implementation, and analyze efforts made to prevent criminal acts by children in motorcycle gangs in Bangun Sari Village, Tanjung Morawa District. The method used in this study is juridical-empirical with a case study approach, which includes interviews with the police and field data analysis. The research findings show that the preventive approach is carried out through active involvement of families, schools, and communities; the repressive approach is applied as a last resort with the principle of ultimum remedium; while the rehabilitative approach focuses on development and restorative justice. The challenges faced include technical limitations such as facilities and human resources, legal obstacles in aligning regulations, and the social impact of the environment and media. This study concludes that collaboration between preventive, repressive, and rehabilitative approaches is essential to create a supportive atmosphere in preventing deviant behavior in children. The police are implementing preventive measures consisting of preventive efforts, namely actions taken before a crime occurs, as well as enforcement measures, namely actions taken after a crime occurs.